2015
DOI: 10.1177/1478210315612655
|View full text |Cite
|
Sign up to set email alerts
|

The needs and difficulties in socializing the young in contemporary China: Early childhood education experts’ perspectives

Abstract: This study was the first of its kind in China to examine early childhood education experts' perspectives on the urgent educational needs of preschool-aged children. Twenty-one nationally and regionally recognized experts, including university professors, practitioners and government officials, participated in interviews. They offered critical evaluations of early educational needs, pointing out the difficulties in socializing young children in the context of dramatic socioeconomic changes, the country's single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Fourthly, research on children's collaboration is imperative in early childhood education. In their study that investigated Chinese early childhood experts' perspectives on the educational needs of preschool children, Hsueh et al (2015) found that ‘the willingness and skills to share, get along and collaborate with others’ was one of the urgent needs in children's learning (p. 127). This finding supports the conclusions of researchers elsewhere.…”
Section: Learning Disposition Of Collaboration In Chinese Early Child...mentioning
confidence: 99%
“…Fourthly, research on children's collaboration is imperative in early childhood education. In their study that investigated Chinese early childhood experts' perspectives on the educational needs of preschool children, Hsueh et al (2015) found that ‘the willingness and skills to share, get along and collaborate with others’ was one of the urgent needs in children's learning (p. 127). This finding supports the conclusions of researchers elsewhere.…”
Section: Learning Disposition Of Collaboration In Chinese Early Child...mentioning
confidence: 99%
“…In our everyday life, one should engage in a wide variety of conversations, ranging from online meetings advancing project collaborations to chitchats forming personal ideologies. However, not everyone is good at socializing [25] and online newcomers face special difficulties as a result of the diffuse, decentralized, and anonymous textbased interactions [2,12]. It is rather challenging for a newcomer to engage in an online multi-party conversation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sangang, the above-mentioned Confucian hierarchical relationships between adults and children, may limit young children's status and practice as citizens. Specifically, as found in Section 8.2.3, tinghua, which means children should follow the instructions of adults and obey the rules of the classroom, remains to be one of the most important cultural constructs to govern how young children think and behave (Chen & Lau, 2020;Hsueh et al, 2015), and for teachers and parents to assess whether children are good citizens or not in the Chinese context.…”
Section: The Problematised Children's Citizenship In Chinamentioning
confidence: 99%